Dividend, Corporate Social Responsibility, And Non-Renewable Energy: Testing Board Diversity Alignments - Muhammad Taufik; Winata Clevertan (Jurnal Internasional Penelitian Bisnis Terapan, 2023)
This paper scrutinizes the alignments of the diversity the board of directors (BOD) towards dividends for tackling information asymmetry, corporate social responsibility (CSR), and non-renewable energy (NRE) consumption in order to gain communities' legitimacy. BOD diversity includes gender, age, education level, nationality, and accounting expertise. Data for this study were collected from 40 firms listed on the Indonesia Stock Exchange from 2017 to 2020, and panel data was then analyzed. The results show that board diversity does not impact dividends, except for foreign directors, but it represents strong governance and zero agency costs. Additionally, the diversity of the board’s gender, nationality, and accounting expertise negatively affects CSR while other variables are insignificant. Board gender and educational level have significant positive effects on NRE consumption (read: exacerbate) while other variables are relatively insignificant. BOD does not serve the community's interests as much as the investor, but they also have agenda to focus on pro-organization. However, sensitivity analysis has documented the board's apathetic attitude toward the environment. In addition to managerial implications, this research also suggests a top-down approach for regulators to remove the potential rhetoric of the renewable energy target.